Working Across Cultural Boundaries: The Many Faces of Diversity. Issue 3 (12th November 2019) - Haskins, Cecilia
ABSTRACT: Most professionals are familiar with the works of Geert Hofstede who developed a framework for cross‐cultural communications in 1980 based on a worldwide survey of employee values between 1967 and 1973, or, Richard D. Lewis and his book, When Cultures Collide, first issued in 1996 and now in its third edition featuring the Lewis model of cross‐cultural communication. Both are based on years of research into the personal attributes one might expect to find in the various countries and offer suggestions on how persons of different backgrounds might use those differences to build relationships and work together. The first person to coin the term culture was Sir Edward Burnett Tylor, an English anthropologist in the 18th century. In his words, culture is "that complex whole which includes knowledge, belief, art, morals, law, custom and any other capabilities and habits acquired by man as a member of society (Taylor 1871, 1)." This article investigates the connections between diversity in systems engineering teams, and quality, innovation, and competitive advantage. I look at the many faces of diversity from a cultural viewpoint and harvest some useful wisdom from the literature and my own experiences as an American living and working in Norway. I conclude that the path to successful appreciation of others comes from maintaining an open mind, alongside careful reflection of the viewpoints of colleagues and friends, and an open attitude toward the value of continuous learning and exploration of the "ologies."